A mode III moving interfacial crack based on strip magneto-electric polarization saturation model. (7th July 2015) - Xia, Xiaodong; Zhong, Zheng
Abstract: This paper deals with a mode III Yoffe-type interfacial crack propagating subsonically under the moving strip magneto-electric saturation model. Nonlinear effects are characterized by different magnetic and electric saturation strips around the crack tip. Employing the extended Stroh method, we obtain generalized moving interfacial dislocation densities analytically under impermeable magneto-electric crack boundary conditions. The generalized intensity factor and local energy release rate with nonlinear effects are derived as fracture parameters for the moving magneto-electro-elastic (MEE) interfacial crack. Numerical results are presented to show the characteristics of fracture dominant parameters with respect to the loading as well as the propagation velocity. In addition, a dimensionless parameter defined by the ratio of the volume fraction of the composite constituents is proposed to evaluate the influences of the MEE bimaterial properties. This research will give us ideas on material selection for optimizing the fracture toughness of MEE composites.